Influence of temperature regimes of synthesis on the structure of glassy GeS2 - Rosola, I.J.; Tsyhyka, V.V.; Tsyhyka, M.V. (Physics and Chemistry of Solid State, 2023)
The effect of synthesis temperature regimes on the structure and some physical properties of glassy germanium disulfide was examined using the methods of dilatometry and Raman scattering of light. It is concluded that the bond angle disorder increases and the formation of stronger Ge–S bonds in the tetrahedral structure depends on the increase in the synthesis temperature of glassy GeS2. Significant changes in the structural grid of glass also occur when the thermal history of the sample varies in the temperature interval of vitrification.